STRATEGI PENETAPAN HARGA: DALAM PERSPEKTIF ISLAM - Fariz, Ferdinan; Alfiah Insani, Nurul; Susanti, Susi; Rohadatul Aisy, Zahra; Sundari, Asri (Jurnal Pelita Nusa, 2024)
Pricing strategy is an important step that allows companies to classify and classify the products and services produced. Prices reflect the total value that customers provide to benefit from owning or using those products and services. From an Islamic perspective, pricing is based on a balance between demand and supply, which is achieved through agreement and willingness between sellers and buyers. In addition, Islamic economic principles such as fairness, honesty, and market balance are the main cornerstones in setting prices. Effective pricing requires a deep understanding of market dynamics, consumer needs, and economic and Sharia principles. By paying attention to all these aspects, companies can determine prices that not only support the achievement of business goals but also uphold the values of justice and mutual benefit.